2008
DOI: 10.1099/vir.0.2008/001131-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparative cell biological analysis reveals only limited functional homology between the NS5A proteins of hepatitis C virus and GB virus B

Abstract: GB virus B (GBV-B) is the closest relative to hepatitis C virus (HCV) with which it shares a common genome organization, however, unlike HCV in humans, it generally causes an acute resolving hepatitis in New World monkeys. It is important to understand the factors regulating the different disease profiles of the two viruses and in this regard, as well as playing a key role in viral RNA replication, the HCV NS5A non-structural protein modulates a variety of host-cell signalling pathways. We have shown previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Even the differential infection profiles between the two viruses could prove helpful in grasping the immune evasion strategies of HCV. For example, the HCV non-structural protein 5A (NS5A), implicated in establishing persistence, modulates the Ras-Erk signaling pathway ( Mankouri et al, 2008a ), whereas the GBV-B NS5A protein does not block this pathway and also differs in its cellular distribution ( Mankouri et al, 2008b ). This suggests that the altered mechanism of NS5A in HCV infection could be responsible for the chronicity of HCV in humans.…”
Section: Hcv Disease In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Even the differential infection profiles between the two viruses could prove helpful in grasping the immune evasion strategies of HCV. For example, the HCV non-structural protein 5A (NS5A), implicated in establishing persistence, modulates the Ras-Erk signaling pathway ( Mankouri et al, 2008a ), whereas the GBV-B NS5A protein does not block this pathway and also differs in its cellular distribution ( Mankouri et al, 2008b ). This suggests that the altered mechanism of NS5A in HCV infection could be responsible for the chronicity of HCV in humans.…”
Section: Hcv Disease In Humansmentioning
confidence: 99%
“…At a functional level, the NS3 protease of GBV-B can correctly process the HCV polyprotein ( Scarselli et al, 1997 ) and HCV/GBVB chimeric NS3 proteins are enzymatically active ( Butkiewicz et al, 2000 ). Interestingly, while both HCV and GBV-B NS5A proteins activate the p13 kinase pathway, HCV NS5A blocks the Ras-Erk pathway, whereas GBV-B NS5A does not ( Macdonald et al, 2003 , 2004 ; Mankouri et al, 2008b ). Despite an error-prone RdRp, very few amino acid substitutions have been observed, limiting the quasispecies variation of GBV-B in infected animals ( McGarvey et al, 2008 ).…”
Section: Characteristics/natural History Of Gbv-b Infectionmentioning
confidence: 99%
“…We and others have shown that GBV-B shares a number of features with HCV, but also exhibits some differences, in terms of genomic organization [8], [9], viral protein maturation [10][12], and virus/host interactions [13][16]. The GBV-B genome contains a single open reading frame encoding a polyprotein which is subsequently cleaved into three structural proteins and seven nonstructural (NS) proteins, among which NS3 to NS5B, only, are required for efficient genome replication in cell culture [17].…”
Section: Introductionmentioning
confidence: 97%
“…We performed a bioinformatics analysis of NS5A protein sequence to understand variations within the protein from different genotypes of HCV. NS5A is a unique protein that has no human or viral homologs other than NS5A of GB virus B (GBV-B) with 21% identity (Mankouri et al, 2008). Herein, UniProt database was used to retrieve NS5A protein sequences from the different genotypes of HCV (i.e.…”
Section: Bioinformaticsmentioning
confidence: 99%
“…Neither NS5A full-length protein nor NS5A-DI has any enzymatic function that can be tested in vitro (Mankouri et al, 2008). However, the DI is known to be interacting with the RNA and DCV (Gao et al, 2010;Hwang et al, 2010).…”
Section: The Effect Of Daclatasvir and Rna On Ns5a-dimentioning
confidence: 99%